Using a word knowledge framework to research vocabulary - Schmitt, Norbert (1997)
The study of vocabulary acquisition is not exactly a new area, but previous research and hypothesizing has failed to produce a coherent overall theory which adequately describes it. This is partly because of the complexity of the subject. One method of reducing the complexity is to work with the individual components of vocabulary knowledge, in an attempt to understand the whole by first better understanding the parts. The word knowledge listing proposed by Nation (1990) is adopted in this thesis as a framework from which to study vocabulary.